Estimation of the emission characteristics of solid-state incandescent light emitting devices by linear regression of spectral radiance. (June 2023) - Samuel, A.; Kuo, Y.
Highlights: A new type of solid state incandescent light emitting device structure is reported. The effect of tungsten embedded in the high-k gate dielectric on the emissive properties was explored. The embedded tungsten did not have negative effect on interface properties and hysteresis. The light emissivity and color corrected temperature of the nano-resistor were calculated. Abstract: The Solid-State Incandescent Light Emitting Device is a broad-band, white-light emitting device that functions by the Joule heating of nano-resistors. The effect of tungsten on the emissive properties of the device was explored by comparing the spectral irradiance of samples made from ultrathin layers of tungsten embedded in zirconium doped hafnium oxide gate dielectrics in single-layer and tri-layer structures. Through linear regression fitting of this data to Planck's law alongside C-V measurements, the relative emissivity of nano-resistors, the radiant power, the total nano-resistor area as well the color corrected temperature were calculated. The embedded tungsten greatly increased the emissivity of the device without negatively affecting interface properties and hysteresis. At the same time, it caused increases in leakage current and charge trapping numbers as well as fewer but large nano-resistors formation due to material mismatch between tungsten and zirconium doped hafnium oxide.